Wnt3a but not CDX-2 expression is associated with differentiated thyroid cancer - Biagini,Gleyne Lopes Kujew (2022)
SUMMARY OBJECTIVE: Thyroid neoplasm incidence has increased worldwide, mostly due to the advancements in medical imaging and screening rates. The aberrant Wnt/β-catenin pathway has been identified as a key mechanism, and it has also been related to the metastatic activity of differentiated thyroid cancer. We aimed to verify the difference in the expression of Wnt3a, a canonical activator of the β-catenin signaling, and CDX-2, a transcription factor upregulated by Wnt/β-catenin pathway, in multinodular goiter and differentiated thyroid cancer and to determine their prognostic value. METHODS: We included 194 thyroid tissue surgical specimen and their clinicopathological data: study group (differentiated thyroid cancer, n=154) and control group (multinodular goiter, n=40). Immunohistochemistry (IHC) was performed on formalin-fixed, paraffin-embedded tissue by the primary antibodies Wnt3a and CDX-2. RESULTS: High Wnt3a expression was significantly associated with differentiated thyroid cancer (p=0.031). CDX-2 was negative in all differentiated thyroid cancer cases (100%) and also in multinodular goiter. Wnt3a expression was significantly associated with tumors ≤20 mm (p=0.044) and with the absence of capsule invasion (p=0.031). The multivariate analyses suggested that older age (≥55), independent of capsular invasion and tumor size, was an independent prognostic factor for Wnt3a expression (p=0.058). CONCLUSIONS: Wnt3a expression but not CDX-2 is correlated with differentiated thyroid cancer samples in comparison to multinodular goiter. Although its prognostic value was limited to tumor size and capsule invasion, a combined model in a panel of immune markers can add accuracy in the classification of challenging thyroid follicular-derived lesions.